Desenvolvimento e caracterização do queijo Santo Giorno, típico do sudoeste do Paraná, produzido com leite cru e fermento endógeno - Roncatti, Roberta (2016)
Two cheese formulations made from raw milk and endogenous yeasts with 30, 60 and 180 days of maturation in two dairy Paraná Southwest were studied to evaluate their quality through physical, physical-chemical, microbiological and sensorial characteristics, as one of the stages of development of a typical regional cheese. The production was accompanied from designing the flowchart processing, where the samples were collected to perform the analysis of proteins, lipids, moisture, ash, carbohydrates, total solids, fat in dry matter, calories; water activity, instrumental texture (hardness, adhesiveness, springiness, cohesiveness, resiliency and chewiness), instrumental color (CIE Lab); microbiological quality was assessed searching for total and thermotolerant coliforms, coagulase positive staphylococci and Salmonella spp.; the acceptance related to sensory characteristics of color, appearance, flavor, texture, taste and purchase intent was evaluated through the structured hedonic scale. This research contributed information relevant to the production process, such as the realization of the viability in freeze-drying lactic acid bacteria yeast isolated from milk in the Southwestern Mesoregion of Parana and the results of the analysis of the cheese showed similarity between formulations, regarding the physical, physical-chemical characterization, moreover good microbiological quality, where the differences between samples of dairy products were not perceived by sensory panelists. Adjustments in standardization related to technological quality control is an extremely important factor for the success of dairy companies and small producers involved in the project and that they have the option of producing the Santo Giorno, a fine cheese, with the great advantage of adding features of region, with high standard of sanitary conditions and with great consumer acceptance of indicative.